Endoscopic ultrasound-guided tissue acquisition for focal liver lesions can be safely performed in patients with ascites - Takano, Yuichi; Tamai, Naoki; Yamawaki, Masataka; Noda, Jun; Azami, Tetsushi; Niiya, Fumitaka; Nishimoto, Fumiya; Maruoka, Naotaka; Yamagami, Tatsuya; Nagahama, Masatsugu (Endoscopy International Open, 2024)
Background and study aims In patients with ascites, percutaneous liver biopsy is generally contraindicated. Because endoscopic ultrasound-guided tissue acquisition (EUS-TA) allows tissue sample obtention from the digestive tract lumen, a biopsy without the intervention of ascites may prevent adverse events (AEs). This study aimed to evaluate the safety of EUS-TA for focal liver lesions in the presence of ascites.Patients and methods A retrospective study was conducted using medical records of cases in which EUS-TA was performed on focal liver lesions between 2016 and 2022. Study participants were classified into two groups: those with ascites and those without it, and the outcomes were compared. The primary outcome was AEs.Results We included 109 cases of EUS-TA for focal liver lesions. Ascites was present in 20.1% of cases (22/109) and absent in 79.8% of cases (87/109). There were no significant differences between the two groups in clinical backgrounds and EUS-TA procedure, although fine-needle biopsy needles were significantly more frequently used in patients without ascites. In the ascites group, puncture without intervening ascites was successful in 90.9% of cases (20/22). The incidence of AEs was 4.5% (1/22) in the ascites group and 1.1% (1/87) in the non-ascites group, showing no significant difference. The two AEs were mild self-limiting abdominal pain.Conclusions In focal liver lesions with ascites, EUS-TA allows biopsy without the intervention of ascites in most cases. The incidence of AEs did not differ significantly between patients with and without ascites.
Keywords: Endoscopic ultrasonography; Tissue diagnosis; Fine-needle aspiration/biopsy; Biliary tract; Intervention EUS